Investigation and Comparative Study Among Various Methods of Contraception Used in Erbil City - R. Abdullah, Ijlal; J. Al-Shamma, Kassim; N. Al-Hassany, Ansam (Iraqi Journal of Pharmaceutical Sciences, 2017)
The objective of this study was to investigate and compare among five different methods of contraception including combined oral contraceptive pills (COC), Depot medroxyprogesterone acetate (DMPA), copper Intrauterine contraceptive device (IUCD), vaginal spermicides and male condom used in Hawler City through estimate of their effect, relative failure rate, percentage of use, adherence and compliance and adverse effects of each contraceptive method. In order to reach to these aims, a retrospective study was conducted in Hawler City in Azadi Health Care Center over a period of 6 months from 22th November, 2010 to 15th May, 2011 during which data collection and subjects follow up for 3 months had been achieved. A convenient sampling method was used to collect 373 married women in their reproductive age group (16-39) years old and 56 husbands. The studied population was allocated into five groups according to contraceptive method used: group (I) included (113) subjects using combined oral contraceptive pills, group (II) included (38) subjects using depot medroxyprogesterone acetate injection, group (III) included (211) subjects using copper intrauterine contraceptive device, group (IV) included (11) subjects using vaginal spermicides and group (V) included (56) subjects using male condom as a contraceptive method. The data necessary for this study had been collected by a direct interview with the subjects and the informations had been recorded on a questionnaire.The study revealed that IUCD had a higher percentage of use among studied sample (49%), regarding the effect DMPA was the most efficient contraceptive method (97.3%) with a lowest failure rate (2.6%), vaginal spermicide and the male condom showed the highest degree of adherence and compliance (100%). The male condom showed highest degree of subject's acceptability (69.9%), whereas DMPA showed lowest acceptability (21%). Regarding gynecological side effects, DMPA showed the highest degree of menstrual irregularity (81.5%) and amenorrhea (65.7%). Breakthrough bleeding, spotting and vaginal infection occurred in the highest percentage among IUCD users (43.1%), (11.8%), (59.2%), respectively. Central nervous system, gastrointestinal and dermatological adverse effects was higher in COC than DMPA users. The extent of weight gain was similar among DMPA and COC users (39.4%) and (39.8%), respectively. While hypertension was less among DMPA users in comparison with COC users. In conclusion, the most popular contraceptive methods used in Hawler City was IUCD, while DMPA was the most efficient contraceptive method in comparing with other methods. Male condom and vaginal spermicidal had been shown the higher rate of adherence and compliance and DMPA showed the lowest failure rate in compare with other methods. Male condom was the most acceptable method for contraception, followed by IUCD, vaginal spermicides, COCs and DMPA respectively. The percentage of menstrual irregularity was highest among DMPA users followed by IUCD users then COCs users, while IUCD showed the highest percentage of vaginal infection followed by DMPA users and then COCs users, and finally in comparison of CNS and GI and dermatological adverse effects of hormonal methods of contraception, COCs showed a higher percentage of occurrences of these adverse effects than DMPA.Key words: contraception,COC, IUCD.